Protocolo operacional padrão para consulta puerperal: avaliação na perspectiva de enfermeiros residentes - Neves, Hanny Karoliny Lima (Universidade Federal do Tocantins, 2020)
The objective was to evaluate the implementing the Standard Operating Protocol on the care practice of resident nurses. The methodology is a cross-sectional descriptive research with a quantitative approach. The study participants are resident nurses enrolled in the residency program in Saúde da Família by Fundação Escola de Saúde Pública de Palmas participants in the implementation of the standardized postpartum consultation instrument. For the implementation assessment, a semi-structured evaluation questionnaire was created and made available online with questions such as: Did the instrument contribute to the assistance provided to the mothers? How did contribute? As a result, 12 resident nurses participated and 42% of these used in three or more consultations. About contribution to consultations, 92% said they had a positive contribution, including, improving professional performance. 50% of participants stated that the contributed was directed to the organization of the consultation, establishing a line of reasoning for the interview. Contribution to physical examination was reported by 33% of participants, improving exam directions. It is concluded that the development of this intervention contributed to the strengthening of actions in the postpartum nursing consultation. The nurses' perceptions regarding the standardized instrument applied were positive in their evaluations. It is an effective method of standard operating protocol and helps in the postpartum clinical examination given the multipurpose work approach to nursing, especially regarding the demands of atenção básica.